Arrhythmogenic Right Ventricular Cardiomyopathy - what do we know? A review of current knowledge state - Radwański, Jan; Pawęska, Wojciech; Dominik, Hanna; Polatowska, Marika; Gadomska, Anna; Kurek, Justyna; Gorzyński, Rafał; Czudy, Zuzanna; Molczyk-Sieńczak, Justyna; Garstka, Michał (Journal of Education, Health and Sport, 2023)
Arrhythmogenic Right Ventricular Cardiomyopathy (ARVC) is an inherited disorder that is responsible for a considerable number of sudden death cases in young athletes. Its pathological hallmark is a progressive loss of myocytes predominantly in the right ventricle and its simultaneous replacement by fibrous and fat tissue, which in turn leads to an increased risk of potentially lethal ventricular arrhythmias to occur. Over a dozen of mutations have been confirmed as genetic basis of ARVC with most of them affecting genes encoding desmosome proteins, however in up to half of all cases the exact etiology is still unknown. By number of studies, it is implied that physical activity is the most significant environmental factor that impacts the development and course of the disease. The main focus of treatment is to prevent sudden cardiac deaths and additionally to moderate arrhythmic events and heart failure.